2015
DOI: 10.1038/ncomms7122
|View full text |Cite
|
Sign up to set email alerts
|

The adhesion GPCR Gpr56 regulates oligodendrocyte development via interactions with Gα12/13 and RhoA

Abstract: In the vertebrate central nervous system, myelinating oligodendrocytes are postmitotic and derive from proliferative oligodendrocyte precursor cells (OPCs). The molecular mechanisms that govern oligodendrocyte development are incompletely understood, but recent studies implicate the adhesion class of G protein-coupled receptors (aGPCRs) as important regulators of myelination. Here, we use zebrafish and mouse models to dissect the function of the aGPCR Gpr56 in oligodendrocyte development. We show that gpr56 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
145
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 64 publications
5
145
0
Order By: Relevance
“…For example, the aGPCR GPR56/ADGRG1 is involved in cortex development, oligodendrocyte development, muscle cell development, innate immunity, and cancer progression (11)(12)(13)(14)(15)(16)(17). Recent studies have highlighted the role of GPR56 in promoting progression of acute myeloid leukemia (18) and progastrin-dependent colon cancer (19) and suggested that a GPR56 inhibitor would be clinically desirable.…”
mentioning
confidence: 99%
“…For example, the aGPCR GPR56/ADGRG1 is involved in cortex development, oligodendrocyte development, muscle cell development, innate immunity, and cancer progression (11)(12)(13)(14)(15)(16)(17). Recent studies have highlighted the role of GPR56 in promoting progression of acute myeloid leukemia (18) and progastrin-dependent colon cancer (19) and suggested that a GPR56 inhibitor would be clinically desirable.…”
mentioning
confidence: 99%
“…Conversely, sustained activation of either PKC or ROCK2 is associated with less efficient differentiation. Indeed, the adhesion receptor GPR56 has recently been shown to inhibit oligodendrocyte myelination in zebrafish via activation of the G␣ 12/13 -RhoA-ROCK pathway (9). Furthermore, down-regulation of the adenylyl cyclase-cyclic-adenosine 3Ј,5Ј-monophosphate (cAMP)-PKA-CREB cascade also impairs oligodendrocyte differentiation (10 -12).…”
mentioning
confidence: 99%
“…That human patients with GPR56/ADGRG1 mutations present with white matter defects underscores the clinical importance of this adhesion GPCR in CNS myelination [68]. Gpr56-dependent OPC proliferation is mediated by Gα 12/13 -RhoA signaling [66,67], although the activating ligand for Gpr56/Adgrg1 in OPCs is currently unknown. In other cellular contexts, Gpr56/Adgrg1 can bind the ECM proteins tissue transglutaminase (TG2) and collagen III [69,70], and in the future it will be interesting to determine if either of these molecules activates Gpr56/Adgrg1 in OPCs.…”
Section: Adhesion Gpcrs In Oligodendrocyte Developmentmentioning
confidence: 99%
“…In the CNS, Gpr17 has been explored as a potential therapeutic target in remyelination either by inhibiting Gpr17 via antagonists or by activating the reserve pool of Gpr17-expressing OPCs to maturation [79,80]. As Gpr17 is enriched in white matter plaques of MS patients and in rodent models of MS, antagonism of Gpr17 or other inhibitory GPCRs may indeed be efficacious in future treatment strategies [57,64,66,67]. Additional GPCRs have been implicated in CNS myelin repair including Cxcr4, Gpr30, endothelin receptors, and sphingosine 1-phosphate receptors [81][82][83][84][85], underscoring the importance of this receptor super-family in myelin health and disease.…”
Section: Pharmacological Implications Of Gpcrs In Myelin Diseasesmentioning
confidence: 99%
See 1 more Smart Citation